Activation energy for the self-metalation reaction of 2H- tetraphenylporphyrin on Cu(111) - Ditze, Stefanie; Stark, Michael Werner; Drost, Martin; Buchner, Florian; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2012)
By simply counting individual molecules in STM images after defined heating steps, the kinetic parameters and the activation energy of a complex surface reaction can be determined quantitatively. This procedure was demonstrated for the metalation of 2H-tetraphenylporphyrin (2HTPP) with substrate atoms on a Cu(111) surface. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Additive fabrication of nanostructures with focused soft X-rays - Späth, Andreas; TU, Fan; Vollnhals, Florian; Drost, Martin; Krick Calderon, Sandra; Watts, Benjamin; Fink, Rainer; Marbach, Hubertus (RSC Advances, 2016)
We report on a novel technique for the fabrication of metallic nanostructures via soft X-ray irradiation of precursor molecules supplied from the gas phase. With this technique we were able to produce localized Co nanostructures with a growth rate and purity competitive with electron beam induced deposition. We demonstrate that our approach exhibits significant selectivity with respect to incident photon energy leading to enhanced growth for resonant absorption energy of the precursor molecule. Based on this finding we propose a unique new pathway of selective deposition from precursor mixtures. Furthermore, we investigated the growth rate with respect to precursor pressure and growth time and discuss the potential resolution limits of this new technique.
EAM Import::2019-03-13

Comparative study of the carbide-modified surfaces C/Mo(110) and C/Mo(100) using high-resolution x-ray photoelectron spectroscopy - Gleichweit, Christoph; Neiß, Christian; Maisel, Sven; Bauer, Udo; Späth, Florian; Höfert, Oliver; Vollnhals, Florian; Drost, Martin; Marbach, Hubertus; Görling, Andreas; Steinrück, Hans-Peter; Papp, Christian (Physical Review B, 2015)
The preparations of single (monolayer) and bulk carbides on the Mo(110) and Mo(100) single crystals are followed in situ at 1200 K using synchrotron-based high-resolution x-ray photoelectron spectroscopy of the C 1s and core Mo 3d(5/2) levels. By comparing the experimental results to first principles calculations using density functional theory, we suggest real-space surface structures for the carbide-modified surfaces. For a monolayer carbide on Mo(110), carbon dimers adsorb in the long-bridge site, most likely at a coverage of 3/8 ML carbon atoms per Mo surface atom. For the bulk carbide, we find a coverage of similar to 0.5ML on the surface, and the calculations show that single carbon atoms are more stable than dimers on the surface. The monolayer carbide on Mo(100) exhibits a coverage of similar to 1ML and agrees with previous studies, while the bulk carbide preparation probably leads to a faceting of the surfac

Coverage dependent disorder-order transition of 2H-tetraphenylporphyrin on Cu(111) - Stark, Michael Werner; Ditze, Stefanie; Drost, Martin; Buchner, Florian; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2013)
In this study, we investigate the peculiar coverage dependent supramolecular arrangement of 2H-tetraphenylporhpyrin (2HTPP) on Cu(111) with scanning tunneling microscopy at room-temperature. At low coverage, "slow" diffusion of individual 2HTPP molecules along the close-packed atomic rows of the substrate is observed, and no supramolecular ordering occurs. However, at higher coverage, the formation of ordered, checkerboard-like domains is found, with two molecules per unit cell at different distances from the surface. This behavior is attributed to a complex interplay of site specific molecule-substrate interaction, mainly the strong interaction between the iminic N atoms and Cu substrate atoms, with intermolecular T-type and π-π interactions. © 2013 American Chemical Society.

Electron-beam induced deposition and autocatalytic decomposition of Co(CO)(3)NO - Vollnhals, Florian; Drost, Martin; TU, Fan; Carrasco Burgos, Esther; Späth, Andreas; Fink, Rainer; Steinrück, Hans-Peter; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2014)
The autocatalytic growth of arbitrarily shaped nanostructures fabricated by electron beam-induced deposition (EBID) and electron beam-induced surface activation (EBISA) is studied for two precursors: iron pentacarbonyl, Fe(CO)(5), and cobalt tricarbonyl nitrosyl, Co(CO)(3)NO. Different deposits are prepared on silicon nitride membranes and silicon wafers under ultrahigh vacuum conditions, and are studied by scanning electron microscopy (SEM) and scanning transmission X-ray microscopy (STXM), including near edge X-ray absorption fine structure (NEXAFS) spectroscopy. It has previously been shown that Fe(CO)(5) decomposes autocatalytically on Fe seed layers (EBID) and on certain electron beam-activated surfaces, yielding high purity, polycrystalline Fe nanostructures. In this contribution, we investigate the growth of structures from Co(CO)(3)NO and compare it to results obtained from Fe(CO)(5). Co(CO)(3)NO exhibits autocatalytic growth on Co-containing seed layers prepared by EBID using the same precursor. The growth yields granular, oxygen-, carbon- and nitrogen-containing deposits. In contrast to Fe(CO)(5) no decomposition on electron beam-activated surfaces is observed. In addition, we show that the autocatalytic growth of nanostructures from Co(CO)(3)NO can also be initiated by an Fe seed layer, which presents a novel approach to the fabrication of layered nanostructures.
Keywords: autocatalytic growth; cobalt tricarbonyl nitrosyl; electron-beam induced deposition; nanofabrication; scanning transmission X-ray microscopy

Exploring the fabrication of Co and Mn nanostructures with focused soft x-ray beam induced deposition - TU, Fan; Späth, Andreas; Drost, Martin; Vollnhals, Florian; Krick Calderon, Sandra; Fink, Rainer; Marbach, Hubertus (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2017)
Focused soft X-ray beam induced deposition of metallic deposits from metal organic precursors is a promising novel technique for additive nanostructure fabrication. In the present work, the authors present a comparative study for deposition and in situ characterization of Co and Mn nanostructures in a scanning transmission x-ray microscope. The authors detect a significant selectivity of the deposition process with respect to the incident photon energy that arises from the enhanced x-ray absorption cross section of the precursor molecules for near-threshold excitation. This effect has been investigated for the L2,3-edges of the respective metal centers of two different precursor molecules as well as the N and O K-edges of the respective ligands. The authors find a photon-limited growth mode for deposition from cobalt tricarbonyl nitrosyl [Co(CO)3NO], while the process is precursor-limited for methylcyclopentadienyl manganese tricarbonyl [MeCpMn(CO)3] possibly due to a comparably low vapor pressure of the latter precursor.
EAM Import::2019-03-14

Fossil biomass preserved as graphitic carbon in a late paleoproterozoic banded iron formation metamorphosed at more than 550°C - Papineau, Dominic; De Gregorio, Bradley T.; Sagar, James; Thorogate, Richard; Wang, Jianhua; Nittler, Larry; Kilcoyne, David A.; Marbach, Hubertus; Drost, Martin; Thornton, Geoff (Journal of the Geological Society, 2019)
Metamorphism is thought to destroy microfossils, partly through devolatilization and graphitization of biogenic organic matter. However, the extent to which there is a loss of molecular, elemental and isotope signatures from biomass during high-temperature metamorphism is not clearly established. We report on graphitic structures inside and coating apatite grains from the c. 1850 Ma Michigamme silicate banded iron formation from Michigan, metamorphosed above 550°C. Traces of N, S, O, H, Ca and Fe are preserved in this graphitic carbon and X-ray spectra show traces of aliphatic groups. Graphitic carbon has an expanded lattice around 3.6 Å, forms microscopic concentrically-layered and radiating polygonal flakes and has homogeneous δ13C values around −22‰, identical to bulk analyses. Graphitic carbon inside apatite is associated with nanometre-size ammoniated phyllosilicate. Precursors of these metamorphic minerals and graphitic carbon originated from ferruginous clayrich sediments with biomass. We conclude that graphite coatings and inclusions in apatite grains indicate fluid remobilization during amphibolite-facies metamorphism of precursor biomass. This new evidence fills in observational gaps of metamorphosed biomass into graphite and supports the existence of biosignatures in the highly metamorphosed iron formation from the Eoarchean Akilia Association, which dates from the beginning of the sedimentary rock record.
CRIS-Team Scopus Importer:2019-07-16

Hungry Porphyrins: Protonation and Self-Metalation of Tetraphenylporphyrin on TiO2(110)-1 x 1 - Köbl, Julia; Wang, Tao; Wang, Cici; Drost, Martin; TU, Fan; Xu, Qian; Ju, Huanxin; Wechsler, Daniel; Franke, Matthias; Pan, Haibin; Marbach, Hubertus; Steinrück, Hans-Peter; et al. (ChemistrySelect, 2016)
We have studied the adsorption and self-metalation of tetraphenylporphyrin (2HTPP) on TiO2(110) -1 x 1 with X-ray Photoelectron Spectroscopy (XPS) and Scanning Tunneling Microscopy (STM). Upon adsorption at room temperature the first monolayer of 2HTPP is protonated by protons from the surface, forming porphyrin diacid (4HTPP(2+)). In STM, single molecules with low mobility and no long-range order were observed. As the surface is heated to 400 K, any unprotonated 2HTPP molecules in the second layer metalate, forming titanyl tetraphenylporphyrin (TiOTPP), but the protonated molecules in the first layer remain. As the surface is heated further to 550 K even the protonated 4HTPP(2+) molecules metalate and only TiOTPP remain on the surface.
Keywords: Adsorption; Porphyrinoids; Oxide Surfaces; Surface Chemistry; Titania

Localized growth of carbon nanotubes via lithographic fabrication of metallic deposits - TU, Fan; Drost, Martin; Szenti, Imre; Kiss, Janos; Konya, Zoltan; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2017)
We report on the fabrication of carbon nanotubes (CNTs) at predefined positions and controlled morphology, for example, as individual nanotubes or as CNT forests. Electron beam induced deposition (EBID) with subsequent autocatalytic growth (AG) was applied to lithographically produce catalytically active seeds for the localized growth of CNTs via chemical vapor deposition (CVD). With the precursor Fe(CO)5 we were able to fabricate clean iron deposits via EBID and AG. After the proof-of-principle that these Fe deposits indeed act as seeds for the growth of CNTs, the influence of significant EBID/AG parameters on the deposit shape and finally the yield and morphology of the grown CNTs was investigated in detail. Based on these results, the parameters could be optimized such that EBID point matrixes (6 × 6) were fabricated on a silica surface whereby at each predefined site only one CNT was produced. Furthermore, the localized fabrication of CNT forests was targeted and successfully achieved on an Al2O3 layer on a silicon sample. A peculiar lift-up of the Fe seed structures as was observed and the mechanism was discussed. Finally, a proof-of-principle was presented showing that EBID deposits from the precursor Co(CO)3NO are also very effective catalysts for the CNT growth. Even though the metal content (Co) of the latter is reduced in comparison to the Fe deposits, effective CNT growth was observed for the Co-containing deposits at lower CVD temperatures than for the corresponding Fe deposits.
EAM Import::2019-03-12

On the magnetic properties of iron nanostructures fabricated via focused electron beam induced deposition and autocatalytic growth processes - TU, Fan; Drost, Martin; Vollnhals, Florian; Späth, Andreas; Carrasco, Esther; Fink, Rainer; Marbach, Hubertus (Nanotechnology, 2016)
We employ Electron beam induced deposition (EBID) in combination with autocatalytic growth (AG) processes to fabricate magnetic nanostructures with controllable shapes and thicknesses. Following this route, different Fe deposits were prepared on silicon nitride membranes under ultra-high vacuum conditions and studied by scanning electron microscopy (SEM) and scanning transmission x-ray microspectroscopy (STXM). The originally deposited Fe nanostructures are composed of pure iron, especially when fabricated via autocatalytic growth processes. Quantitative near-edge x-ray absorption fine structure (NEXAFS) spectroscopy was employed to derive information on the thickness dependent composition. X-ray magnetic circular dichroism (XMCD) in STXM was used to derive the magnetic properties of the EBID prepared structures. STXM and XMCD analysis evinces the existence of a thin iron oxide layer at the deposit-vacuum interface, which is formed during exposure to ambient conditions. We were able to extract magnetic hysteresis loops for individual deposits from XMCD micrographs with varying external magnetic field. Within the investigated thickness range (2-16 nm), the magnetic coercivity, as evaluated from the width of the hysteresis loops, increases with deposit thickness and reaches a maximum value of ∼160 Oe at around 10 nm. In summary, we present a viable technique to fabricate ferromagnetic nanostructures in a controllable way and gain detailed insight into their chemical and magnetic properties.
EAM Import::2019-03-08

On the Principles of Tweaking Nanostructure Fabrication via Focused Electron Beam Induced Processing Combined with Catalytic Growth Processes - Drost, Martin; TU, Fan; Vollnhals, Florian; Szenti, Imre; Kiss, Janos; Marbach, Hubertus (Small Methods, 2017)
Novel pathways to use a focused electron beam in ultrahigh vacuum in combination with catalytic growth protocols are explored for the fabrication of well-defined nanostructures. Thereby, the basic process is the local deposition of material from different precursor molecules (Co(CO)3 NO, Fe(CO)5). This can be realized with a focused electron beam by direct deposition of the precursor or by a chemical modification of the substrate, such that it becomes activated toward the decomposition of the precursor. For both methods, autocatalytic growth (AG) processes can occur, yielding the deposition of additional material. Interestingly, significantly different chemical selectivities for the two precursors are found, which can drastically change upon subtle changes of the surface. It is demonstrated that AG can be tweaked by the choice of the substrate/precursor combination. One possibility to quench catalytic activity of a substrate is the preparation of a thin layer of organic molecules, here porphyrins, which enables the fabrication of hybrid metal–organic nanostructures with line widths below 20 nm. Based on these findings, corresponding techniques are developed which exploit (auto)catalytic effects for the controlled fabrication of nanostructures. These results indicate that every substrate is applicable to electron beam induced surface activation by preparation of a thin porphyrin layer.
EAM Import::2019-03-08

Region-selective Deposition of Core–Shell Nanoparticles for 3 D Hierarchical Assemblies by the Huisgen 1,3-Dipolar Cycloaddition - Etschel, Sebastian; Portilla Berlanga, Luis; Kirschner, Johannes; Drost, Martin; Marbach, Hubertus; Tykwinski, Rik; Halik, Marcus (Angewandte Chemie International Edition, 2015)
A method for the region-selective deposition of nanoparticles (NPs) by the Huisgen 1,3-dipolar cycloaddition is presented. The approach enables defined stacking of various oxide NPs in any order with control over layer thickness. Thereby the reaction is performed between a substrate, functionalized with a self-assembled monolayer of an azide-bearing phosphonic acid (PA) and aluminum oxide (AlOx) NPs functionalized with an alkyne bearing PA. The layer of alkyne functionalized AlOx NPs is then used as substrate for the deposition of azide-functionalized indium tin oxide (ITO) NPs to provide a binary stack. This progression is then conducted with alkyne-functionalized CeO2 NPs, yielding a ternary stack of NPs with three different NP cores. The stacks are characterized by AFM and SEM, defining the region-selectivity of the deposition technique. Finally, these assemblies have been tested in devices as a dielectric to form a capacitor resulting in a dramatic increase in the measured capacitance.

Temperature-dependent chemical and structural transformations from 2H-tetraphenylporphyrin to copper(II)-tetraphenylporphyrin on Cu(111) - Xiao, Jie; Ditze, Stefanie; Chen, Min; Buchner, Florian; Stark, Michael Werner; Drost, Martin; Steinrück, Hans-Peter; Gottfried, J. Michael; Marbach, Hubertus (Journal of Physical Chemistry C, 2012)
Temperature-dependent chemical and structural changes of a submonolayer of 2H-tetraphenylporphyrin (2HTPP) on Cu(111) were studied with photoelectron spectroscopy (XPS/UPS) and scanning tunneling microscopy (STM). 2HTPP reacts with Cu atoms from the substrate to form copper(II)-tetraphenylporphyrin (CuTPP). This metalation reaction starts at about 400 K and was investigated at various temperatures up to 500 K. At room temperature, adsorbed 2HTPP adopts an orientation with the molecular plane parallel to the substrate; the same holds for its reaction product CuTPP after annealing to 400 K. In contrast, annealing at 450 K yields a tilted orientation of CuTPP, as indicated by STM and supported by C 1s XPS shifts and changes in the Cu(111) surface state. Subsequent annealing at 500 K restores a flat-lying orientation; however, the appearance of the complex in STM images differs from the original appearance of CuTPP. In summary, 2HTPP undergoes three irreversible transformations upon annealing on Cu(111), a metalation reaction to CuTPP followed by two intramolecular structural changes. © 2012 American Chemical Society.